2020
DOI: 10.1101/2020.10.07.330381
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cortical beta oscillatory activity evoked during reactive balance recovery scales with perturbation difficulty and individual balance ability

Abstract: I.AbstractCortical beta oscillations (13-30 Hz) reflect sensorimotor cortical activity, but have not been fully investigated in balance recovery behavior. We hypothesized that more challenging balance conditions would lead to greater recruitment of cortical sensorimotor brain regions for balance recovery. We predicted that beta power would be enhanced when balance recovery is more challenging, either due to more difficult perturbations or due to lower intrinsic balance ability. In 19 young adults, we measured … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 76 publications
8
12
0
Order By: Relevance
“…We then computed the mean baseline beta power (-500 to 0ms before perturbation onset) and the peak of the perturbation-evoked change in beta power (100-500ms) relative to baseline for each participant. Based on our previous study which found differences between early and later portions of motor cortical beta activity responses as a function of balance ability in younger adults (Ghosn et al, 2020), we further identified peak perturbation-evoked beta power within an early (100-300ms) and later (300-500ms) time window of the response.…”
Section: Quantification Of Cortical Beta Powermentioning
confidence: 94%
See 4 more Smart Citations
“…We then computed the mean baseline beta power (-500 to 0ms before perturbation onset) and the peak of the perturbation-evoked change in beta power (100-500ms) relative to baseline for each participant. Based on our previous study which found differences between early and later portions of motor cortical beta activity responses as a function of balance ability in younger adults (Ghosn et al, 2020), we further identified peak perturbation-evoked beta power within an early (100-300ms) and later (300-500ms) time window of the response.…”
Section: Quantification Of Cortical Beta Powermentioning
confidence: 94%
“…Twenty-four perturbations of equal magnitude (7.5 cm, 16.0 cm/s, 0.12 g) were delivered in the forwards direction to elicit a backwards center of mass displacement relative to the base of support. The scaling of these perturbation parameters was selected to ensure that platform deceleration did not occur until 500 ms after perturbation onset to minimize changes in cortical and motor output originating from a deceleration response (Ghosn et al, 2020;McIlroy & Maki, 1994). Because we aimed for each participant to sustain identical perturbations, we selected this lower-level perturbation magnitude as a level of postural destabilization that could be successfully completed by most older adults using a feet-in-place strategy (Figure 1).…”
Section: Balance Perturbationsmentioning
confidence: 99%
See 3 more Smart Citations